Keanekaragaman Hayati di Lahan Rehabilitasi Taman Nasional Meru Betiri dan Implikasi Kebijakannya: Kasus Desa Wonosari - Alvian Febry Anggana; Sigit Andy Cahyono; Casimerus Yudi Lastiantoro (Jurnal Ilmu Lingkungan, 2019)
After the looting and destruction of forest land in the Merubetiri National Park area were effortS to restore the area to its original condition. Various efforts were made involving the community in the rehabilitation of Meru Betiri National Park land. One indicator of the success of land rehabilitation is increasing biodiversity. The purpose of this study was to determine biodiversity in the rehabilitation area of Meru Betiri National Park. The method used uses a 100-200 m striped line combination at each location for vegetation data collection. Vegetation analysis by calculating type frequency, species density, species dominance, important value index, species diversity index, species richness index and distribution pattern. The results showed that there were 14 types of vegetation in 11 families in 4 common observation plots and jackfruit plants (Artocarpus heterophyllus) and showed adaptability and these plants were needed by the community. Based on the results of the study, the INP value of the Wonoasri plot was 103.27% Pete (Parkia speciosa), Bonangan plot was Jackfruit (Artocarpus heterophyllus) of 154.18%, Donglo plot of Jackfruit (Artocarpus heterophyllus) was 133.22%, and Jackfruit Pletes (Artocarpus heterophyllus) of 262.41%. For this reason, it is necessary to do new types of enhancements and compaction of spacing on each rehabilitation plot so that the value of diversity and species richness can increase, so that the success of rehabilitation can be seen.